2018
DOI: 10.1016/j.chroma.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of antibodies upon adsorption onto hydrophobic interaction chromatography surfaces

Abstract: Differential scanning calorimetry was established for in-situ measurement of the transition temperatures of antibodies when adsorbed on hydrophobic interaction chromatography media. This method is also suitable for non-transparent media, which is an advantage over spectroscopic methods that cannot be used in many cases due to large background signals. The three transition temperatures of an antibody were lowered when the molecule was adsorbed onto Phenyl and Butyl functionalized Toyopearl particles as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…The free energy of conformational entropy, G c (F), which describes the stability of the protein with regards to the hydrophobic interactions in the protein core was selected in the CDRs, framework regions, and the constant domains. This is supported by published literature where protein stability has been reported to play a pivotal role in HIC binding [50]. Other important energy descriptors of note were the number of estimated water molecules surrounding the surface, W(F), and the entropy energy from the first shell of water, ∆G w , representing the energy contribution from interactions between polar residues and surrounding water molecules.…”
Section: Structural Descriptors Important For Prediction Of Hic Rtsupporting
confidence: 70%
“…The free energy of conformational entropy, G c (F), which describes the stability of the protein with regards to the hydrophobic interactions in the protein core was selected in the CDRs, framework regions, and the constant domains. This is supported by published literature where protein stability has been reported to play a pivotal role in HIC binding [50]. Other important energy descriptors of note were the number of estimated water molecules surrounding the surface, W(F), and the entropy energy from the first shell of water, ∆G w , representing the energy contribution from interactions between polar residues and surrounding water molecules.…”
Section: Structural Descriptors Important For Prediction Of Hic Rtsupporting
confidence: 70%
“…Therefore, the heterogeneous binding nature of the resins has to be a key element for the greater molar enthalpy values at low concentration. Conformational changes of the antibody upon adsorption are also probable at low surface coverage, as founded by Bayer and Jungbauer, [35] but they depend on the hydrophobicity of the ligands. TP PA has a greater enthalpy change possibly because of the greater number of binding possibilities when compared to MSS.…”
Section: Adsorption Enthalpymentioning
confidence: 84%
“…Furthermore, it has been reported that antibodies can go through conformational changes upon their adsorption on colloidal particles or hydrophobic surfaces, depending on protein structure and surface characteristics [ 24 , 25 ]. In particular, antibodies can experience reversible conformational changes upon adsorption on HIC resins with likely more significant changes for less stable domains (e.g., Fab and CH2) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%